Synthesis and Biological Activity of (Z) –n-(5-Benzylidene-4-oxo-2-substituted- phenylthiazolidin-3-yl)-5-((1, 3-dioxoisoindolin-2-yl)methyl)-2-hydroxybenzamide - M. C. Patel; Dhameliya (E-Journal of Chemistry)
5-((1, 3-Dioxoisoindolin-2-yl)methyl-2-hydroxybenzohydrazide (1) undergoes facile condensation with aromatic aldehydes to afford the corresponding N'-substituted-phenyl-5-((1,3-dioxoisoindolin-2-yl) methyl)-2-hydroxybenzohydrazide (2a-h) in good yields. Cyclocondensation of compounds (2a-h) with thioglycolic acid yields 5-((1,3-dioxoisoindolin-2-yl) methyl)-2-hydroxy-N-(4-oxo-2-substituted phenylthiazolidin-3-yl)benzamide (3a-h). These (3a-h) compounds were further reacted with benzaldehyde in the presence of sodium ethanolate affords, (Z) –N-(5-benzylidene-4-oxo-2-substituted phenyl-thiazolidin-3-yl)-5-((1,3-dioxoisoindolin-2-yl)methyl)-2-hydroxybenzamdie(4a-h). The structures of these compounds were established on the basis of analytical and spectral data. All the newly synthesized compounds were evaluated for their antibacterial and antifungal activities.